75PDynamics of ctDNA in patients with NSCLC. (7th November 2019) - Zhabina, A S; Mjslik, A; Moiseenko, F; Moiseenko, V; Stepanova, M
Abstract: Background: For many years, researchers have tried to find more effective ways to find out if a person has cancer, and find it at an early stage, when it is most curable. One idea that is gaining popularity is called liquid biopsy. Methods: From 2016 to 2018 we studied 1050 patients with non-small-cell lung cancer (NSCLC). Before the treatment and then every 2 months after, whole blood was taken for qualitative assessment of ctDNA dynamics by RT-PCR. The aim of the study was to assess the relationship between the presence of mEGFR ctDNA in tumor tissue and blood plasma. Results: The study involved 1050 patients, of which 462 cases were represented by adenocarcinoma of NSCLC. EGFR mutations were detected in 145/462 targeted agents (31.38%). The molecular genetic profile ctDNA was represented by the following mutations for women 33/59 (55.9%): ex19del - 20 (60.6%), L858R - 13 (39.4%); for men 13/19 (68.42%). No association was found in the detectability of the mutation with sex, age, localization of metastases, or stage. Among patients with stage III only the L858 mutation (3/3) was found. The T790m resistance mutation was detected in the primary plasma sample in 8/79 cases (10.1%). After 2 months of gefitinib, EGFR-mutation-positive ctDNA were detected in blood plasma in 23.3% of cases (13/56). Of the 42 patients in whom the ctDNA was detected before treatment, after 2 months of therapy it was detectedin only 6/42. Thus, the disappearance of the mutation was observed in 85.71% (36/42). Median progression-free survival for patients who retained ctDNA after 2 months was 16.25 months (Cl 95% 11.24 - 19.94), and for patients in whom the mutation disappeared after 2 months it was 21.10 (Cl 19.21 - 22.98). The results of the study showed that blood plasma analysis is an appropriate the method of EGFR mutation detection: sensitivity 59.2%, specificity 98.8%, prognostic positive result 91.3%, prognostic negative result 91.6%. Conclusions: The integration and liquid biopsy might complement the gold standard tissue testing and is a promising candidate for studying NSCLC. ctDNA assay might be applied in identifying actionable genomic alterations, dynamically monitoring response and resistance to targeted agents, prescreening early-stage lung cancer, and tracking the spatiotemporal evolution of lung cancer. Legal entity responsible for the study: The authors. Funding: Has not received any funding. Disclosure: All authors have declared no conflicts of interest.